2011
DOI: 10.1007/978-3-642-22200-9_14
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Measurement of Trust-Related Behavior in Trust-Neutral and Trust-Critical Situations

Abstract: In this paper we present results of a user study that we conducted with 21 subjects to investigate whether initial user trust is accompanied by unconscious bodily responses which enable more objective measurements than user reports. In particular, we recorded the user's eye gaze and heart rate to evaluate whether users respond differently when interacting with a web page that is supposed to build initial trust as opposed to a web page that lacks this capability. Our results indicate that there are significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In relation to the trust rate, the two-tailed t-test showed there were significant differences where the trust rates in both the high trust conditions, HTLCL (M=$1617.9, SD=$448. 5 HTHCL))).…”
Section: Preliminary Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the trust rate, the two-tailed t-test showed there were significant differences where the trust rates in both the high trust conditions, HTLCL (M=$1617.9, SD=$448. 5 HTHCL))).…”
Section: Preliminary Analysis and Resultsmentioning
confidence: 99%
“…In relation to using physiological signals to measure trust, researchers found that when they examined eye gaze during web page browsing, people maintained more continuous focus on the pages that they trusted [5]. Also, the ability to measure cognitive load via GSR values is explored.…”
Section: Background Literaturementioning
confidence: 99%
“…observable user behaviors. In our earlier work [35], we investigated various physiological patterns as an indicator of trust felt by a user when viewing web pages. As a next step, we will concentrate on the identification of behavioral factors from which experience-based user trust might be derived in ubiquitous display environments, such as the time spent in front of a public display or the number of downloads.…”
Section: Resultsmentioning
confidence: 99%
“…For example, human observers tend to prefer items that a trusted individual looks at, as opposed to an untrusted one [King et al 2011]. They also make shorter duration eye fixations while viewing untrusted websites [Leichtenstern et al 2011]. Individuals cooperating in a game look at each other approximately twice as long as individuals engaged in competition [Foddy 1978].…”
Section: Related Workmentioning
confidence: 99%